Expression of Escherichia coli glycogen branching enzyme in an Arabidopsis mutant devoid of endogenous starch branching enzymes induces the synthesis of starch‐like polyglucans. (24th February 2016) - Boyer, Laura; Roussel, Xavier; Courseaux, Adeline; Ndjindji, Ofilia M.; Lancelon‐Pin, Christine; Putaux, Jean‐Luc; Tetlow, Ian J.; Emes, Michael J.; Pontoire, Bruno; D' Hulst, Christophe; Wattebled, Fabrice
Abstract: Starch synthesis requires several enzymatic activities including branching enzymes (BEs) responsible for the formation of α(1 → 6) linkages. Distribution and number of these linkages are further controlled by debranching enzymes that cleave some of them, rendering the polyglucan water‐insoluble and semi‐crystalline. Although the activity of BEs and debranching enzymes is mandatory to sustain normal starch synthesis, the relative importance of each in the establishment of the plant storage polyglucan (i.e. water insolubility, crystallinity and presence of amylose) is still debated. Here, we have substituted the activity of BEs in Arabidopsis with that of the Escherichia coli glycogen BE (GlgB). The latter is the BE counterpart in the metabolism of glycogen, a highly branched water‐soluble and amorphous storage polyglucan. GlgB was expressed in the be2 be3 double mutant of Arabidopsis, which is devoid of BE activity and consequently free of starch. The synthesis of a water‐insoluble, partly crystalline, amylose‐containing starch‐like polyglucan was restored in GlgB‐expressing plants, suggesting that BEs' origin only has a limited impact on establishing essential characteristics of starch. Moreover, the balance between branching and debranching is crucial for the synthesis of starch, as an excess of branching activity results in the formation of highly branched, water‐soluble, poorly crystalline polyglucan. Abstract : The synthesis of starch‐like polyglucan was restored by expressing the structural gene of Escherichia coli glycogen branching enzyme (GlgB) in a starchless mutant of Arabidopsis thaliana lacking endogenous starch branching enzymes. The results point out the importance of controlling the balance between branching and debranching activities to sustain starch synthesis.